SANDUR ANTARA TONTONAN DAN TUNTUNAN - Arif Hidajad; Autar Abdillah; Indar Sabri; Welly Suryandoko (Jurusan Sendratasik FBS Unesa, 2022)
This research tries to express analytically a phenomenon of transformation era with it’s influence and result. The influence relates to value. This new value of selenium can change life of social in structure, and also arranges implementation of public. Artistry of public as stripper public culture product, more or less experiencing friction of either in function and also its existence. This research using sociological theatre tries to analyzes the product existence with modern culture product. Modern idea that producing practical patterned thinking, individualist as a result of system value which transform. The friction is aspect function of from solidarity and emancipation of supporter public to different value. Artistry existence of public as social institute sub hardly determines continuous tradition of the past. Ledok Kulon as a outskirts of course also has arranging value. Influence of television as a product of transformation era of course also brings as result of other in arranging value. Existence of Sandur as public culture product has meaning in transformation era with its globalization. Economic and other social element science of course related to causality generated. Presence of public theatre of Sandur in the middle of public is being experiences friction of the value, be a real interesting study to be expressed. Artistry of public that is full value expressed through phonetic symbol in artistry, returns to emerging and deflecting stays in change to arrange value. Existence of Sandur public theatre is reasoning of importance of value in this transformation era, of course television becomes side effect as media and also as influence to value. Importance function and collective life of public becomes reasoning of this art, in form and also philosophy.